Not a matter of parental choice but of social justice obligation: Children are owed measles vaccination. (19th September 2018) - Bester, Johan C.
Abstract: This article presents arguments that reframe the discussion on vaccination ethics. The correct starting point for discussions on vaccination ethics is not what society owes parents, but rather what society owes children. Drawing on the justice theory of Powers and Faden, two conclusions are defended by presenting and defending a set of arguments. First, a just society is obligated to protect its children against serious vaccine‐preventable diseases such as measles through adequate levels of vaccination. Second, this obligation of the just society rests on identifiable individuals and institutions: parents, healthcare professionals, government, and vaccine producers have important obligations in this regard. This removes vaccination out of the realm of individual or parental discretion, and situates it in the realm of societal obligation. Children are owed vaccination, society is obligated to provide it. If parents cannot or will not provide it, society ought to respond.